A escolha de um estabelecimento federal de ensino médio e seus significados para jovens e famílias de diferentes meios sociais: um estudo no IFNMG – Campus Janaúba - Bruna Tatianne Moura de Queirós (2022)
The research aims to understand the choice for an integrated high school in a Federal Institute made by young people and their families and the senses given by these subjects, considering their social groups. We held the research in Instituto Federal do Norte de Minas Gerais – IFNMG, Campus Avançado Janaúba, with students from the Technical Course on Internet Technology, integrated to High School. The study is in the area of Sociology of Education, dialoguing with studies on school choice and the Bourdieusian theory. First, we mapped out the socioeconomic and cultural profiles of IFNMG-Janaúba students admitted in the course between 2017 and 2020, applying questionnaires to them and their families. After, we chose the classes of 2017 and 2019 to investigate the process of school choice. We held focus groups with students, according to parental educational level, and individual interviews with them and their mothers. We start from the hypothesis that IFNMG has a socioeconomically heterogeneous group of students with different motivations to join the institution. We have seen that, though participant students were not as heterogeneous as previously thought, their profile is different from those of other local public schools and the population of Janaúba, mainly, by a slightly larger school capital of the families. Most students seem to be from low-income groups (though not from the most vulnerable strata) or lower strata of middle classes. Regarding school choice, though motivated by different expectations, the main one was the search for a quality education and, consequently, the possibility to prepare for university admission processes/ENEM. Few students chose the integrated high school considering primarily the technical training. We observed family participation in this process, with meaningful variations (from the non- participation of parents when the choice is focused on the young person, passing by various types of shared choice between parents and children, up to the family imposition to the school), which are related to the parental volume of cultural and informational capital. On one hand, we have identified in more educated families more “strategic” choices, some clearly guided by the possibility of joining the public-school quotas in higher education; on the other, in less educated families, we have seen a less active and informed choice. In this context, the actions of young people based on their own sociability network stand out. Paying attention to the young person as a subject of school choice, in the different social groups, is one of the contributions of this study. This opens a door to different meanings to this choice, including, besides academic aspects, socio-identity issues. We also highlight the importance of integrated high school to the social mobility of low-income youngsters and, consequently, the need to increase the access of this public to such educational opportunity.